Productivity of winter oilseed rape depending on its nitrogen and water use efficiency - Rutkowska, Agnieszka (Polish Journal of Agronomy, 2019)
This paper presents the results of 11 years of field experimentconcerning winter oilseed rape in Eastern Poland. Theaim of the study was to characterise rape production dependingon the nitrogen and water use efficiency. Oilseed rape was fertilisedwith increasing doses of nitrogen, i.e. 50, 100, 150, 200and 250 kg N ha-1. It was found that rapeseed yields increasedstatistically significantly to 3.33 t ha-1 at a rate of 200 kg N ha-1.This dose guaranteed: nitrogen uptake of 155 kg N ha-1, nitrogenuse efficiency of 78%, nitrogen surplus of 45 kg N ha-1, wateruse efficiency of 8.4 kg ha-1 mm-1 and nitrogen utilisation efficiencyof 22 kg kg-1. Increasing the nitrogen rate in the long termto 250 kg N ha-1 proved to be unjustified because it did not causea significant increase in the yield or water use efficiency, while itsignificantly increased the nitrogen uptake, its surplus in the soiland reduced the efficiency of nitrogen from fertilisers utilisation.